2003
DOI: 10.1002/app.12955
|View full text |Cite
|
Sign up to set email alerts
|

Deformation, yield and fracture of elastomer‐modified polypropylene

Abstract: ABSTRACT:In recent decades, great attention has been devoted to the toughening of isotactic poly(propylene) (PP) with elastomers such as ethylene-propylene rubber (EPR). The most important reasons for this interest are the moderate cost and favorable properties of PP. This article is focused on the role of EPR in the deformation and fracture mechanism of PP/EPR blends with different volume fractions of elastomer phase. Differential scanning calorimetry (DSC), tensile tests, and microscopy techniques were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 18 publications
4
33
0
1
Order By: Relevance
“…Thus, one may conclude that the fracture toughness measurements for all the nanocomposites (including unfilled HDPE) cannot satisfy the LEFM requirements. This is similar to what proposed by Zebarjad et al 25 during determination of fracture toughness of PP and its blend and what reported by Hooley and Moore 26 In fact, they showed that plane strain fracture toughness of PE can be achieved at room temperature if the sample thickness is more than 255 mm. 26 The simple fact that the injection machine necessary to mold such thick samples does not yet exist, it means it would be absurd to compare hypothetical fracture results obtained on samples of such thickness.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, one may conclude that the fracture toughness measurements for all the nanocomposites (including unfilled HDPE) cannot satisfy the LEFM requirements. This is similar to what proposed by Zebarjad et al 25 during determination of fracture toughness of PP and its blend and what reported by Hooley and Moore 26 In fact, they showed that plane strain fracture toughness of PE can be achieved at room temperature if the sample thickness is more than 255 mm. 26 The simple fact that the injection machine necessary to mold such thick samples does not yet exist, it means it would be absurd to compare hypothetical fracture results obtained on samples of such thickness.…”
Section: Resultssupporting
confidence: 88%
“…25,[33][34][35][36][37][38] Since the scientists who studied fracture behavior of the materials believe that the main part of fracture energy is due to making plastic zone or stress whitening zone in front of precrack, the current research has been concentrated on this subject. Figure 8 points out the effect of SWZ on fracture toughness for the materials.…”
Section: Stress Whitening Zone and Fracture Toughnessmentioning
confidence: 99%
“…With regarding the results of our previous works [22][23][24][25][26][27][28][29] and current study, the effect of combination of CaCO 3 and EPR on deformation and fracture behaviour of PP can be summarised similar to what proposed by Zebarjad et al [29] for PP-EPR-GF. In fact, addition CaCO 3 leads the dominant fracture mechanism of PP from shear yielding to crazing.…”
Section: Resultssupporting
confidence: 58%
“…Traditional toughness reinforcement of PP by the addition of rubber 1,2 or elastomer 3 decreases the strength and rigidity of the materials; this especially weakens the thermal stability of the materials. In this study, we focused on a new method for enhancing the toughness of PP by adding organophilic montmorillonite (OMMT) while retaining the material's high strength, rigidity, and thermal stability.…”
Section: Introductionmentioning
confidence: 99%